Effect of rs10440833 polymorphism in the CDKAL1 gene on insulin secretion in type 2 diabetes patients - Raed Farzan (Journal of King Saud University: Science, 2024)
In the present generation, type 2 diabetes mellitus (T2DM) has become a common disease with the same trend in the Saudi Arabia due to many factors. Apart from environmental factors, genetic factors are also playing the major role. In this context, this study has design to screen a polymorphism related to T2DM and which was not studied yet in the Saudi Arabia and this study was designed by selecting rs10440833 polymorphism in CDKAL1 gene. The aim of this study was to execute the genetic association with rs1044883 polymorphism in the CDKAL1 gene in Saudi patients diseased with T2DM. In this study, 60 T2DM patients and 60 controls were selected and genotyping was carried with PCR-RFLP analysis using ACIL restriction enzyme. The obtained data was calculated with SPSS software and the tables were generated. The current study results confirmed, that some of the clinical parameters significantly differ between T2DM cases and control subejcts (p < 0.05). Genotype and allele frequencies showed negative association (p > 0.05). However, both regression and ANOVA analysis was also showed negative association (p > 0.05). In conclusion, the rs10440833 polymorphism is not associated in the Saudi Arabian T2DM patients and this polymorphism has no role.